Holistic Approach in Natural Dye Batik Customer Loyalty based on Social, Environmental, Service, Price Awareness Through Customer Satisfaction - Nugroho, Wahyu; Tjahjaningsih, Endang (Jurnal Manajemen dan Kewirausahaan, 2025)
Customers’ loyalty in the alami batik industry is influenced by holistic principles based on social and cultural factors, environmental awareness, service quality, and price. Tests were conducted to determine the relationship between factors that influence customer satisfaction and loyalty. The calculation results show a significant relationship between variables. Environmental awareness has a strong positive impact on price perception (path coefficient = 0.696, t-statistic = 6.174), indicating that environmentally conscious customers are willing to pay more for environmentally friendly products. Service quality significantly affects customer satisfaction (path coefficient = 0.316, t-statistic = 2.213), highlighting the importance of good service in enhancing customer experience. Price also shows a strong positive effect on customer satisfaction (path coefficient = 0.603, t-statistic = 4.142), emphasizing that competitive and fair prices enhance customer satisfaction. Social and cultural factors affect service quality (path coefficient = 0.416, t-statistic = 2.763), enhancing customer perceptions of the overall service experience. Furthermore, customer satisfaction greatly influences customer loyalty (path coefficient = 0.811, t statistic = 15.054). The holistic approach shows that customer satisfaction and loyalty to natural dye batik products are influenced by the synergy of socio-cultural factors, environmental awareness, service quality, and price. The integration of these four constructs creates a complete customer experience, strengthening emotional relationships and sustainability values, thereby encouraging long-term loyalty.